Method for manufacturing solid sulfide electrolyte
By using liquid without hydroxyl part to heat treatment with solid electrolyte precursor, the safety hazards and low conductivity of liquid electrolytes in lithium secondary batteries are solved, and a high conductivity and high purity sulfur silver germanium ore-type crystal structure is achieved. The preparation of solid sulfide electrolyte improves battery performance and safety.
Patent Information
- Application Number
- CN202380046876.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-24
- Filing Date
- 2023-06-23
- Publication Date
- 2025-01-14
AI Technical Summary
Commonly used liquid electrolytes in existing lithium secondary batteries have safety risks, such as leakage and fire risks, and the use of ethanol as a solvent leads to a low conductivity of solid sulfide electrolytes.
A mixture of liquid without hydroxyl moieties and solid electrolyte precursors was heat treated to generate a solid sulfide electrolyte with a high conductivity, a sulfur-silver germanium ore-type crystal structure.
The conductivity of solid sulfide electrolytes is improved, safety is enhanced and yield loss of solid sulfide electrolytes is reduced, providing electrolytes with higher purity and higher performance.
Smart Images

Figure CN119318045A_ABST
Abstract
Description
[0001] Technical Field and Background Art
[0002] The present invention relates to a method for producing a solid sulfide electrolyte and a solid sulfide electrolyte obtainable by said method.
[0003] As the development of small and lightweight electronic products, electronic equipment, communication equipment, etc. has rapidly progressed, and the demand for electric vehicles has widely emerged in terms of environmental issues, there is a demand for improving the performance of secondary batteries used as power sources for these products. Among these secondary batteries, lithium secondary batteries have become the focus of high-performance batteries due to their high energy density and high reference electrode potential.
[0004] However, the electrolyte conventionally used in lithium secondary batteries is a liquid electrolyte such as an organic solvent. Therefore, safety problems such as leakage of the electrolyte and the risk of fire may continue to occur.
[0005] Recently, solid-state batteries including solid electrolytes instead of liquid electrolytes have been used to improve the safety characteristics of lithium secondary batteries and have attracted much attention. For example, solid electrolytes are generally safer than liquid electrolytes due to non-flammable or flame-retardant properties.
[0006] The solid electrolyte may include an oxide-based solid electrolyte, a polymer-based electrolyte, and a sulfide-based electrolyte. Since the sulfide-based electrolyte has a higher lithium ion conductivity range than the oxide-based solid electrolyte and the polymer-based solid electrolyte, a sulfide-based electrolyte, such as a sulfide-based solid electrolyte having an argyrodite-type crystal structure, is generally used.
[0007] Conventionally, a method for making a solid sulfide electrolyte uses ethanol as a solvent or liquid. Typically, the precursors of LiCl, P2S5, and Li2S are dissolved in ethanol, the mixture is stirred, the solvent is removed, and the resulting mixture is calcined into a resulting solid sulfide electrolyte such as Li6PS5Cl and Li6PS5Br. Examples of this liquid-based method using ethanol are described in US 2020 / 0119394 A1 and US 2019 / 0173127 A1. US 2019 / 0074544 A1 describes a similar synthesis route using Li3PS4, LiCl, and Li2S as precursors dissolved in ethanol. Ethanol has been considered to be a suitable solvent for synthesizing Li6PS5Cl because the precursors are completely dissolved in ethanol, thereby driving the reaction to form a solid sulfide electrolyte. However, the inventors have observed that alcohols (such as ethanol or methanol) as solvents are detrimental to the resulting conductivity of the solid sulfide electrolyte.
[0008] Therefore, there is a need to provide a method for producing a solid sulfide electrolyte that uses a liquid other than ethanol and does not produce a solid sulfide electrolyte with low conductivity.
[0009] An object of the present invention is to provide a method for producing a solid sulfide electrolyte.
[0010] Another object of the present invention is to provide a solid sulfide electrolyte obtainable by said method.
[0011] Another object of the present invention is to provide a solid sulfide electrolyte having an argyrodite-type crystal structure.
[0012] Another object of the present invention is to provide a battery comprising the solid sulfide electrolyte. Summary of the invention
[0013] In a first aspect, the objects of the present invention are achieved by providing a method for producing a solid sulfide electrolyte by providing a solid electrolyte precursor mixture and a liquid that does not contain hydroxyl moieties.
[0014] The present inventors surprisingly found that by mixing a solid electrolyte precursor mixture with an organic liquid other than ethanol or methanol and then subjecting it to a heat treatment to obtain a solid sulfur electrolyte, the resulting conductivity of the solid sulfur electrolyte is higher than that of solid argyrodite obtained after mixing the solid electrolyte precursor mixture with ethanol or methanol.
[0015] Without wishing to be bound by any theory, the inventors believe that the alcohol solvent nucleophilically attacks the PS4 3- unit, thereby decomposing the sulfur-based solid electrolyte and forming PO4 3- 、PSO3 3- and / or PS2O2 3- Decomposition products, such as Li3PO4. These decomposition products are detrimental to the resulting conductivity of the solid sulfide electrolyte. One possible solution is to recrystallize the solid sulfide electrolyte in ethanol to obtain a pure compound that exhibits high conductivity (ACS Appl. Energy Mater. 2018, 1, 8, 3622-3629). However, the decomposition of the solid sulfur electrolyte or solid sulfur electrolyte precursor will result in an overall loss of solid sulfide electrolyte yield.
[0016] In another aspect, the present invention provides a solid sulfide electrolyte obtainable by the method according to the present invention.
[0017] In another aspect, the present invention provides a solid sulfide electrolyte having an argyrodite-type crystal structure.
[0018] In another aspect, the present invention provides a battery comprising a solid sulfide electrolyte according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 : XRD spectra of EX1-5 and CEX1-2 before calcination using different liquids (ACN = acetonitrile, DME = dimethoxyethane, EA = ethyl acetate, DMF = dimethylformamide).
[0020] Figure 2 : XRD spectra of EX1-5 and CEX1-2 after calcination using different liquids (ACN = acetonitrile, DME = dimethoxyethane, EA = ethyl acetate, DMF = dimethylformamide).
[0021] Figure 3 : Before and after calcination, EX1 31 P NMR, and CEX1 before and after calcination 31 P NMR. DETAILED DESCRIPTION
[0022] In the accompanying drawings and the following specific embodiments, preferred embodiments are described in detail to practice the present invention. Although the present invention is described with reference to these specific preferred embodiments, it should be understood that the present invention is not limited to these preferred embodiments. In contrast, the present invention includes many alternatives, modifications and equivalent forms, which will become apparent by considering the following specific embodiments and the accompanying drawings.
[0023] As used herein and in the claims, the term "comprising" should not be interpreted as being limited to the means listed thereafter; it does not exclude other elements or steps. It needs to be interpreted as specifying the presence of the features, integers, steps or components mentioned, but does not exclude the presence or addition of one or more other features, integers, steps or components or groups thereof. Therefore, the scope of the expression "a composition comprising component A and component B" should not be limited to a composition consisting only of component A and component B. This means that with respect to the present invention, the only relevant components of the composition are A and B. Therefore, the terms "comprising" and "including" encompass the more restrictive terms "consisting essentially of" and "consisting of".
[0024] As used herein, the term "solid-state battery" refers to a battery cell or battery that includes only solid-state components or substantially solid-state components such as solid electrodes (eg, anodes and cathodes) and a solid electrolyte.
[0025] As used herein, the term "argyrodite crystal structure" refers to a crystal structure having a crystal structure or system similar to the naturally occurring Ag8GeS6 and Li7S6 (argyrodite). Argentite crystals may be orthorhombic, having a Pna21 space group and having a unit cell of a=15.149, b=7 476, c=10 589 [Å]; Z=4. In some embodiments, the argyrodite crystal structure may also be determined empirically, for example by X-ray diffraction using CuKα-rays, by observing peaks around 2θ=15.5±1°, 18±1°, 26±1°, 30.5±1°, and 32±1°.
[0026] As referred to herein, ionic conductivity refers to ionic conductivity measured by electrochemical impedance spectroscopy (EIS) at 25°C. It is preferably determined on a pressed sample with a stainless steel plunger, where a pressure of 5 T is applied on a sample with a diameter of 10 mm and a total sample mass of 120 mg, where a pressure of 80 kg / cm 2 A suitable conductivity analyser is a potentiostat with a frequency analyser, such as available from Biologic.
[0027] As referred to herein, the electronic conductivity refers to the electronic conductivity determined at 25° C. It is preferably determined on a pressed sample with a stainless steel plunger, wherein a pressure of 5 T is applied on a sample having a diameter of 10 mm and a total sample mass of 120 mg, wherein a pressure of 80 kg / cm 2 Preferably, the ionic conductivity is measured via stepwise potentiostatic polarization at 0.2 V, 0.4 V, 0.6 V and 0.8 V.
[0028] As referred to herein, X-ray diffraction (XRD) refers to XRD experiments performed using a Bruker D8 Advanced diffractometer with Cu radiation (λ1 = 1.54056 Å, λ2 = 1.54439 Å).
[0029] Manufacturing method
[0030] As discussed above, in a first aspect, the present invention provides a method for making a solid sulfide electrolyte, the method comprising the consecutive steps of:
[0031] (i) providing an electrolyte precursor mixture comprising a solid electrolyte precursor mixture and a liquid, the solid electrolyte precursor mixture comprising Li2S, Li3PS4 and LiX, the liquid not comprising a hydroxyl moiety;
[0032] (ii) mixing the electrolyte precursor mixture obtained in step (i); and
[0033] (iii) heat treating the mixed electrolyte precursor mixture obtained in step (ii) to obtain a solid sulfide electrolyte having an argyrodite-type crystal structure;
[0034] wherein X is a halogen selected from F, Cl, Br, I or a combination thereof.
[0035] As used herein, the term "solid electrolyte precursor mixture" refers to an electrolyte precursor mixture that is substantially free of any liquid. The term "substantially free of liquid" means that the solid electrolyte precursor mixture contains less than 10% by weight of liquid, preferably less than 7.5% by weight, more preferably less than 5% by weight, even more preferably less than 2.5% by weight, and most preferably less than 1% by weight, based on the total weight of the solid electrolyte precursor mixture. In a more preferred embodiment, the solid electrolyte precursor mixture contains less than 1000ppm of liquid, preferably less than 500ppm, more preferably less than 100ppm, even more preferably less than 50ppm, and most preferably less than 10ppm, based on the total weight of the solid electrolyte precursor mixture.
[0036] In the context of the present invention, a liquid is considered to be an organic or aqueous compound that is liquid under standard temperature and pressure conditions as defined by IUPAC. Accordingly, boiling points and melting points are considered to be boiling points and melting points under standard atmospheric pressure, i.e., 101325 Pa. As will be appreciated by those skilled in the art, the presence of an organic liquid can be determined via thermogravimetric analysis (TGA) or nuclear magnetic resonance (NMR) spectroscopy, and the presence of an aqueous liquid (such as water) can be determined via Karl Fisher titration.
[0037] As used herein, the term "solid sulfide electrolyte" refers to a solid sulfide electrolyte that is substantially free of any liquid. The term "substantially free of liquid" means that the solid sulfide electrolyte contains less than 10% by weight of liquid, preferably less than 7.5% by weight, more preferably less than 5% by weight, even more preferably less than 2.5% by weight, and most preferably less than 1% by weight, based on the total weight of the solid sulfide electrolyte. In a more preferred embodiment, the solid sulfide electrolyte contains less than 1000 ppm of liquid, preferably less than 500 ppm, more preferably less than 100 ppm, even more preferably less than 50 ppm, and most preferably less than 10 ppm, based on the total weight of the solid sulfide electrolyte.
[0038] As understood by those skilled in the art, every crystal structure of Li3PS4 can be used in the method of the present invention, specifically the γ-polymorph, α-polymorph and β-polymorph of Li3PS4.
[0039] A preferred embodiment of the present invention is the method according to the present invention, wherein the solid sulfide electrolyte is represented by formula (I):
[0040] Li 7-y PS 6-y X y (I)
[0041] Wherein y=0.8-1.7. As will be appreciated by those skilled in the art, when y is from 0.8 to 1.7, a solid sulfide electrolyte having an argyrodite-type crystal structure can be obtained. In a more preferred embodiment, y is from 0.8 to 1.7, preferably y is 0.9 or greater and 1.6 or less, and more preferably y is 1.0 or greater and 1.4 or less.
[0042] A very preferred embodiment is the method according to the invention, wherein the solid sulfide electrolyte is represented by formula (II)
[0043] Li6PS5X(II).
[0044] A preferred embodiment is the process according to the invention, wherein X=F, Cl, Br, I or a combination thereof; preferably X=Cl, Br or a combination thereof; more preferably X=Cl.
[0045] According to a preferred embodiment of the present invention, a solid sulfide electrolyte is provided, wherein at least 50 mol % of X represents Cl, preferably at least 80 mol % of X represents Cl, most preferably X represents Cl.
[0046] According to a preferred embodiment of the present invention, a solid sulfide electrolyte is provided, wherein X represents F, Cl, Br, I or a combination thereof, and wherein at least 50 mol % of X represents Cl, preferably at least 80 mol % of X represents Cl.
[0047] According to a preferred embodiment of the present invention, a solid sulfide electrolyte is provided, wherein at least 50 mol % of X represents F, preferably at least 80 mol % of X represents F, most preferably X represents F.
[0048] According to a preferred embodiment of the present invention, a solid sulfide electrolyte is provided, wherein X represents F, Cl, Br, I or a combination thereof, and wherein at least 50 mol % of X represents Br, preferably at least 80 mol % of X represents Br.
[0049] According to a preferred embodiment of the present invention, a solid sulfide electrolyte is provided, wherein at least 50 mol % of X represents Br, preferably at least 80 mol % of X represents Br, most preferably X represents Br.
[0050] According to a preferred embodiment of the present invention, a solid sulfide electrolyte is provided, wherein X represents F, Cl, Br, I or a combination thereof, and wherein at least 50 mol % of X represents Br, preferably at least 80 mol % of X represents Br.
[0051] According to a preferred embodiment of the present invention, a solid sulfide electrolyte is provided, wherein at least 50 mol % of X represents I, preferably at least 80 mol % of X represents I, and most preferably X represents I.
[0052] According to a preferred embodiment of the present invention, a solid sulfide electrolyte is provided, wherein X represents F, Cl, Br, I or a combination thereof, and wherein at least 50 mol % of X represents I, preferably at least 80 mol % of X represents I.
[0053] A highly preferred embodiment is the process according to the invention, wherein X=F, Cl, Br or I; preferably X=Cl or Br; more preferably X=Cl.
[0054] A preferred embodiment is the process according to the present invention, wherein the molar ratio of Li2S:Li3PS4:LiX is between (0.5-1.5):(0.5-1.5):(0.5-1.5), preferably between (0.75-1.25):(0.75-1.25):(0.75-1.25), more preferably between (0.9-1.1):(0.9-1.1):(0.9-1.1). In a more preferred embodiment, the molar ratio of Li2S:Li3PS4:LiX is between (0.95-1.05):(0.95-1.05):(0.95-1.05), preferably between (0.98-1.02):(0.98-1.02):(0.98-1.02), more preferably between (0.99-1.01):(0.99-1.01):(0.99-1.01). In a highly preferred embodiment, the molar ratio of Li2S:Li3PS4:LiX is about 1:1:1.
[0055] A preferred embodiment is the process according to the present invention, wherein the molar ratio of Li:P:S:X is between (5-7):(0.5-1.5):(4-6):(0.5-1.5), preferably between (5.5-6.5):(0.75-1.25):(4.5-5.5):(0.75-1.25), more preferably between (5.75-6.25):(0.9-1.1):(4.75-5.25):(0.9-1.1). In a more preferred embodiment of the present invention, the molar ratio of Li:P:S:X is between (5.9-6.1):(0.95-1.05):(4.9-5.1):(0.95-1.05), preferably between (5.95-6.05):(0.98-1.02):(4.95-5.05):(0.98-1.02), more preferably between (5.98-6.02):(0.99-1.01):(4.98-5.02):(0.99-1.01). In a highly preferred embodiment, the molar ratio of Li:P:S:X is about 6:1:5:1.
[0056] As will be understood by those skilled in the art, a liquid that does not contain a hydroxyl moiety is any liquid that does not contain a hydroxyl functional group (also referred to as a hydroxyl functional group or -OH group) as a functional part of the liquid. Examples of liquids that do not meet this definition are alcohols, such as ethanol and methanol, water, or glycols.
[0057] A preferred embodiment is a method according to the invention, wherein the liquid not comprising a hydroxyl moiety is an organic liquid. In certain preferred embodiments, the liquid not comprising a hydroxyl moiety is an aprotic liquid. As will be appreciated by those skilled in the art, an aprotic liquid is a liquid in which hydrogen atoms are not directly attached to electronegative atoms such as O and N. In other words, an aprotic liquid does not contain OH or NH functional moieties. In certain preferred embodiments, an aprotic liquid is a liquid lacking acidic protons.
[0058] A more preferred embodiment is a method according to the present invention, wherein the liquid not comprising a hydroxyl moiety is selected from: hydrocarbons, esters, ketones, aldehydes, ethers, nitrile, amines, amides, carbonates, sulfones, sulfoxides, sulfonates, mercaptans, fluorine-based compounds and combinations thereof; preferably the group consisting of: amides, esters, ethers, nitrile, aromatic hydrocarbons and combinations thereof, most preferably selected from: amides, ethers, nitrile, aromatic hydrocarbons and combinations thereof. In certain preferred embodiments, the liquid not comprising a hydroxyl moiety is selected from: aromatic hydrocarbons, esters, ethers, nitrile, amides, sulfoxides, mercaptans and combinations thereof, preferably the liquid not comprising a hydroxyl moiety is selected from: aromatic hydrocarbons, esters, ethers, nitrile, amides, sulfoxides and mercaptans. Examples of hydrocarbons are straight or branched hydrocarbons, such as straight or branched pentane, straight or branched hexane, straight or branched octane, straight or branched nonane, straight or branched decane, straight or branched undecane and straight or branched dodecane. Other examples of hydrocarbons are cyclic alkanes such as cyclopentane, cyclohexane, cycloheptane or cyclooctane. Other examples of hydrocarbons are aromatic hydrocarbons such as benzene, toluene, o-xylene, m-xylene or p-xylene. Other examples of hydrocarbons in the present invention are alkyl halides such as chloroform, chloromethane or dichloromethane. Examples of esters are methyl acetate or ethyl acetate (EtOAc). Examples of ketones are acetone or butanone. Examples of ethers are dimethyl ether, ethyl ether, methyl ethyl ether, tetrahydrofuran or dimethoxyethane (DME). An example of carbonate is dimethyl carbonate. Examples of amines are pyridine, aniline, hydrazine, triethylamine, diethylamine, monoethylamine, ethylenediamine or ammonia. Examples of amides are dimethylformamide (DMF) or N-methyl-2-pyrrolidone. An example of sulfoxide is dimethyl sulfoxide (DMSO). An example of sulfone is sulfolane. An example of thiol is butanethiol. An example of nitrile is acetonitrile. Examples of fluorine-based compounds are benzene fluoride; heptane fluoride; 2,3-dihydroperfluoropentane and 1,1,2,2,3,3,4-heptafluorocyclopentane.
[0059] In a highly preferred embodiment, the liquid not comprising hydroxyl moieties is selected from: DMF, EtOAc, DME, CH3CN, xylene, DMSO, butanethiol, ethylenediamine and combinations thereof, preferably selected from: DMF, EtOAc, DME, CH3CN, xylene and combinations thereof, most preferably selected from: DMF, DME, CH3CN, xylene and DMSO.
[0060] As demonstrated in the attached examples, a solid sulfur electrolyte is not formed before the heat treatment of the mixed electrolyte precursor mixture, and therefore a liquid not containing a hydroxyl moiety is used as a mixing medium for the electrolyte precursor mixture. The inventors were surprised to find that one or more precursors and / or solid sulfide electrolytes do not have to be completely dissolved in a liquid not containing a hydroxyl moiety. In contrast, when ethanol was used as a liquid, all precursors and solid sulfide electrolytes were completely dissolved, and the formation of solid sulfide electrolytes was observed before calcination. However, as demonstrated in the attached examples, using ethanol as a liquid in a method for making a solid sulfide electrolyte is harmful to the ionic and / or electronic conductivity of the solid sulfide electrolyte.
[0061] In a preferred embodiment, the amount of the solid electrolyte precursor mixture exceeds 0.5 wt % based on the total weight of the solid electrolyte precursor mixture and the liquid not containing the hydroxyl moiety, preferably exceeds 1 wt %, more preferably exceeds 2.5 wt % based on the total weight of the solid electrolyte precursor mixture and the liquid not containing the hydroxyl moiety. In a preferred embodiment, the amount of the solid electrolyte precursor mixture is less than 15 wt % based on the total weight of the solid electrolyte precursor mixture and the liquid not containing the hydroxyl moiety, preferably less than 10 wt %, more preferably less than 7.5 wt % based on the total weight of the solid electrolyte precursor mixture and the liquid not containing the hydroxyl moiety. In a preferred embodiment, the amount of the solid electrolyte precursor mixture is between 0.5 wt % and 15 wt % based on the total weight of the solid electrolyte precursor mixture and the liquid not containing the hydroxyl moiety, preferably between 1 wt % and 10 wt %, more preferably between 2.5 wt % and 7.5 wt % based on the total weight of the solid electrolyte precursor mixture and the liquid not containing the hydroxyl moiety.
[0062] In a preferred embodiment, the electrolyte precursor mixture comprises at least 90 wt % of the liquid that does not contain hydroxyl moieties, based on the total weight of the electrolyte precursor mixture, more preferably at least 92 wt % of the liquid that does not contain hydroxyl moieties, and most preferably at least 94 wt % of the liquid that does not contain hydroxyl moieties, based on the total weight of the electrolyte precursor mixture.
[0063] In a preferred embodiment, the electrolyte precursor mixture comprises between 90 wt % and 99 wt % of the liquid that does not contain hydroxyl moieties, based on the total weight of the electrolyte precursor mixture, more preferably between 92 wt % and 98 wt % of the liquid that does not contain hydroxyl moieties, and most preferably between 94 wt % and 97 wt % of the liquid that does not contain hydroxyl moieties, based on the total weight of the electrolyte precursor mixture.
[0064] In a preferred embodiment, the electrolyte precursor mixture comprises between 0.5 wt % and 15 wt % of the solid electrolyte precursor mixture, preferably between 1 wt % and 10 wt % of the solid electrolyte precursor mixture, more preferably between 2.5 wt % and 7.5 wt % of the solid electrolyte precursor mixture, based on the total weight of the electrolyte precursor mixture.
[0065] In certain highly preferred embodiments, the electrolyte precursor mixture consists of a solid electrolyte precursor mixture and a liquid that does not contain hydroxyl moieties.
[0066] A preferred embodiment is the method according to the invention, wherein step (ii) further comprises the following steps:
[0067] (ii) a mixing the electrolyte precursor mixture obtained in step (i), and
[0068] (ii)b Drying the mixed electrolyte precursor obtained in step (ii)a to obtain a solid electrolyte mixture.
[0069] As used herein, the term "solid electrolyte mixture" refers to an electrolyte mixture that is substantially free of any liquid. The term "substantially free of liquid" means that the solid electrolyte mixture comprises less than 10% by weight of liquid, preferably less than 7.5% by weight, more preferably less than 5% by weight, even more preferably less than 2.5% by weight, and most preferably less than 1% by weight, by the total weight of the solid electrolyte mixture. In a more preferred embodiment, the solid electrolyte mixture comprises less than 1000ppm of liquid, preferably less than 500ppm, more preferably less than 100ppm, even more preferably less than 50ppm, and most preferably less than 10ppm, by the total weight of the solid electrolyte mixture.
[0070] A preferred embodiment is the method according to the invention, wherein the electrolyte precursor mixture is mixed at a mixing speed between 100 rpm and 1500 rpm, preferably between 200 rpm and 1000 rpm, most preferably between 400 rpm and 800 rpm.
[0071] A preferred embodiment is the method according to the present invention, wherein the mixing of the electrolyte precursor mixture in step (ii) and / or step (ii) a is carried out with a mixing time of at least 1 minute, preferably at least 0.5 hours, more preferably at least 1 hour, even more preferably at least 2 hours, even more preferably at least 5 hours, most preferably at least 10 hours. A preferred embodiment is the method according to the present invention, wherein the mixing is carried out with a mixing time of less than 72 hours, preferably less than 60 hours, more preferably less than 50 hours, even more preferably less than 40 hours, even more preferably less than 36 hours, most preferably less than 30 hours. A preferred embodiment is the method according to the present invention, which is carried out by mixing the solid electrolyte precursor mixture with a mixing time between 1 hour and 72 hours, preferably between 2 hours and 60 hours, more preferably between 10 hours and 30 hours.
[0072] According to a highly preferred embodiment of the present invention, the mixing of the solid electrolyte precursor mixture in step (ii) and / or step (ii)a is carried out as follows:
[0073] - a mixing speed between 100 rpm and 1500 rpm, preferably between 200 rpm and 1000 rpm, most preferably between 400 rpm and 800 rpm; and
[0074] The mixing time is between 1 and 72 hours, preferably between 2 and 60 hours, more preferably between 10 and 30 hours.
[0075] A preferred embodiment is the method according to the invention, wherein the mixing of the electrolyte precursor mixture is carried out at a temperature of at least 5° C., preferably at least 10° C., more preferably at least 15° C. A preferred embodiment is the method according to the invention, wherein the mixing is carried out at a temperature of less than 50° C., preferably less than 40° C., more preferably less than 30° C. A preferred embodiment is the method according to the invention, wherein the mixing is carried out at a temperature between 5° C. and 50° C., preferably between 10° C. and 40° C., more preferably between 15° C. and 30° C.
[0076] A preferred embodiment is the drying of the mixed electrolyte precursor in step (ii)b, wherein the liquid not containing hydroxyl moieties is removed by heating the mixed electrolyte precursor obtained in step (ii)a. Preferably, the liquid not containing hydroxyl moieties is removed by heating under reduced pressure. As will be appreciated by those skilled in the art, when the liquid not containing hydroxyl moieties has a (relatively) high boiling point, the heating temperature of the mixed electrolyte precursor obtained in step (ii)a should be increased as much as possible and / or the pressure should be reduced as much as possible, so as to more easily remove the liquid not containing hydroxyl moieties. Examples of drying of the mixed electrolyte precursor (but not limited to the present invention) are rotary evaporation, vacuum distillation and / or drying in an oven or vacuum oven.
[0077] A preferred embodiment is the process according to the invention, wherein the heat treatment in step (iii) is carried out at a temperature of at least 100°C, preferably at least 200°C, more preferably at least 300°C, more preferably at least 400°C, even more preferably at least 450°C, most preferably at least 500°C. A preferred embodiment is the process according to the invention, wherein the heat treatment in step (iii) is carried out at a temperature of less than 1000°C, preferably less than 900°C, more preferably less than 800°C, even more preferably less than 700°C, even more preferably less than 600°C, most preferably less than 550°C. A preferred embodiment is the process according to the invention, wherein the heat treatment in step (iii) is carried out at a temperature between 100°C and 1000°C, preferably between 300°C and 700°C, more preferably between 350°C and 650°C.
[0078] As understood by those skilled in the art, the heat treatment of the mixed electrolyte mixture in step (iii) to obtain a solid sulfide electrolyte having an argyrodite-type crystal structure is also referred to as calcining the solid electrolyte mixture to form a solid sulfide electrolyte having argyrodite-type crystals.
[0079] A preferred embodiment is the process according to the invention, wherein the heat treatment in step (iii) is carried out under an inert atmosphere, preferably an argon atmosphere, or under an atmosphere comprising hydrogen sulfide gas, preferably consisting of hydrogen sulfide gas.
[0080] A preferred embodiment is the method according to the present invention, wherein the heat treatment of the solid electrolyte mixture in step (iii) is at least 1 minute, preferably at least 0.5 hours, more preferably at least 1 hour, even more preferably at least 1.5 hours, most preferably at least 2 hours. A preferred embodiment is the method according to the present invention, wherein the heat treatment of the solid electrolyte mixture in step (iii) is less than 48 hours, preferably less than 24 hours, more preferably less than 18 hours, even more preferably less than 12 hours, most preferably less than 10 hours. A preferred embodiment is the method according to the present invention, wherein the heat treatment of the solid electrolyte mixture in step (iii) is between 0.5 hours and 24 hours, preferably between 1 hour and 12 hours, more preferably between 1.5 hours and 10 hours.
[0081] Solid sulfide electrolyte
[0082] The second aspect of the present invention is to provide a solid sulfide electrolyte that can be obtained by the method according to the present invention. As understood by those skilled in the art, all embodiments related to the method for manufacturing a solid sulfide electrolyte according to the present invention are also applicable to the solid sulfide electrolyte that can be obtained by the method according to the present invention.
[0083] A preferred embodiment is a solid sulfide electrolyte according to the present invention, which is substantially free of a phase formed by Li2S, LiCl, Li4P2S6 and / or Li3PS4, as determined by XRD, wherein the peak intensity of Li2S, LiCl, Li4P2S6 and / or Li3PS4 is less than 30%, preferably less than 25%, more preferably less than 20%, even more preferably less than 10%, most preferably less than 5% of the peak intensity of Li6PS5Cl. According to a preferred embodiment, the solid sulfide electrolyte according to the present invention has a purity of at least 70%, preferably at least 75%, more preferably at least 80%, even more preferably at least 90%, most preferably at least 95%, as determined by XRD.
[0084] A preferred embodiment is a solid sulfide electrolyte according to the present invention having an XRD pattern around 2θ=15.5±1°, 18±1°, 26±1°, 30.5±1° and 32±1° using CuK α-rays.
[0085] A preferred embodiment is a solid sulfide electrolyte according to the present invention which contains substantially no PO4 3- (such as Li3PO4) as determined by NMR (preferably by 31 P NMR) determined, where PO4 3-The peak area of ? is less than 30% relative to the total area, preferably less than 25% relative to the total area, more preferably less than 20% relative to the total area, even more preferably less than 10% relative to the total area, and most preferably less than 5% relative to the total area. A preferred embodiment is a solid sulfide electrolyte according to the present invention, which substantially does not contain PSO3 3- (such as Li3PSO3) as determined by NMR (preferably by 31 P NMR) determined, where PSO3 3- The peak area of ? is less than 30% relative to the total area, preferably less than 25% relative to the total area, more preferably less than 20% relative to the total area, even more preferably less than 10% relative to the total area, and most preferably less than 5% relative to the total area. A preferred embodiment is a solid sulfide electrolyte according to the present invention, which substantially does not contain PS2O2 3- (such as Li3PS2O4) as determined by NMR (preferably by 31 P NMR) determined that PS2O2 3- The peak area of ? is less than 30% relative to the total area, preferably less than 25% relative to the total area, more preferably less than 20% relative to the total area, even more preferably less than 10% relative to the total area, and most preferably less than 5% relative to the total area. A preferred embodiment is a solid sulfide electrolyte according to the present invention, which substantially does not contain P2S7 4- The phase formed, as determined by NMR (preferably by 31 P NMR) determined, where P2S7 4- The peak area of ? is less than 30% relative to the total area, preferably less than 25% relative to the total area, more preferably less than 20% relative to the total area, even more preferably less than 10% relative to the total area, and most preferably less than 5% relative to the total area. According to a preferred embodiment, the solid sulfide electrolyte according to the present invention has a peak area of ? as measured by NMR (preferably 31 P NMR) determined at least 70% pure, preferably at least 75% pure, more preferably at least 80% pure, even more preferably at least 90% pure, most preferably at least 95% pure. As will be appreciated by those skilled in the art, PS4 3- With a signal between 80 ppm and 90 ppm, preferably about 85 ppm, as indicated by 31 PNMR determined; PO4 3- With a signal between 5 ppm and 15 ppm, preferably about 10 ppm, as indicated by 31 P determined by NMR; PSO3 3-With a signal between 30 ppm and 40 ppm, preferably about 35 ppm, as indicated by 31 P determined by NMR; PS2O2 3- With a signal between 65 ppm and 75 ppm, preferably about 70 ppm, as indicated by 31 P determined by NMR; and P2S7 4- With a signal between 90 ppm and 100 ppm, preferably about 95 ppm, as indicated by 31 Determined by P NMR.
[0086] A preferred embodiment is a solid sulfide electrolyte according to the invention having an ionic conductivity of at least 1 mS / cm, preferably at least 1.5 mS / cm, most preferably at least 2 mS / cm. A preferred embodiment is a solid sulfide electrolyte according to the invention having an ionic conductivity of less than 5 mS / cm, more preferably less than 4 mS / cm, most preferably less than 3 mS / cm. A preferred embodiment is a solid sulfide electrolyte according to the invention having an ionic conductivity between 1 mS / cm and 5 mS / cm, preferably between 1.5 mS / cm and 4 mS / cm, most preferably between 2 mS / cm and 3 mS / cm.
[0087] A preferred embodiment is a solid sulfide electrolyte according to the present invention having a -7 mS / cm, preferably at least 1x10 -6 mS / cm, most preferably at least 1x10 -5 A preferred embodiment is a solid sulfide electrolyte according to the present invention, which has an electronic conductivity of less than 1x10 -2 mS / cm, preferably less than 1x10 -3 mS / cm, most preferably less than 1x10 -4 A preferred embodiment is a solid sulfide electrolyte according to the present invention, which has an electronic conductivity of between 1x10 -7 mS / cm vs 1x10 -2 mS / cm, preferably between 1x10 -6 mS / cm vs 1x10 -3 mS / cm, preferably between 1x10 -5 mS / cm vs 1x10 -4 Electronic conductivity between mS / cm.
[0088] The third aspect of the present invention is to provide a solid sulfide electrolyte having an argyrodite crystal structure. As understood by those skilled in the art, all embodiments related to the method for manufacturing the solid sulfide electrolyte according to the present invention and all embodiments related to the solid sulfide electrolyte that can be obtained by the method for manufacturing the solid sulfide electrolyte are also applicable to the solid sulfide electrolyte having an argyrodite crystal structure according to the present invention.
[0089] A preferred embodiment is a solid sulfide electrolyte according to the present invention, which is substantially free of a phase formed by Li2S, LiCl, Li4P2S6 and / or Li3PS4, as determined by XRD, wherein the peak intensity of Li2S, LiCl, Li4P2S6 and / or Li3PS4 is less than 30%, preferably less than 25%, more preferably less than 20%, even more preferably less than 10%, most preferably less than 5% of the peak intensity of Li6PS5Cl. According to a preferred embodiment, the solid sulfide electrolyte according to the present invention has a purity of at least 70%, preferably at least 75%, more preferably at least 80%, even more preferably at least 90%, most preferably at least 95%, as determined by XRD.
[0090] A preferred embodiment is a solid sulfide electrolyte according to the present invention having an XRD pattern around 2θ=15.5±1°, 18±1°, 26±1°, 30.5±1° and 32±1° using CuK α-rays.
[0091] A preferred embodiment is a solid sulfide electrolyte according to the present invention which contains substantially no PO4 3- (such as Li3PO4) as determined by NMR (preferably by 31 P NMR) determined, where PO4 3- The peak area of ? is less than 30% relative to the total area, preferably less than 25% relative to the total area, more preferably less than 20% relative to the total area, even more preferably less than 10% relative to the total area, and most preferably less than 5% relative to the total area. A preferred embodiment is a solid sulfide electrolyte according to the present invention, which substantially does not contain PSO3 3- (such as Li3PSO3) as determined by NMR (preferably by 31 P NMR) determined, where PSO3 3-The peak area of ? is less than 30% relative to the total area, preferably less than 25% relative to the total area, more preferably less than 20% relative to the total area, even more preferably less than 10% relative to the total area, and most preferably less than 5% relative to the total area. A preferred embodiment is a solid sulfide electrolyte according to the present invention, which substantially does not contain PS2O2 3- (such as Li3PS2O4) as determined by NMR (preferably by 31 P NMR) determined that PS2O2 3- The peak area of ? is less than 30% relative to the total area, preferably less than 25% relative to the total area, more preferably less than 20% relative to the total area, even more preferably less than 10% relative to the total area, and most preferably less than 5% relative to the total area. A preferred embodiment is a solid sulfide electrolyte according to the present invention, which substantially does not contain P2S7 4- The phase formed, as determined by NMR (preferably by 31 P NMR) determined, where P2S7 4- The peak area of ? is less than 30% relative to the total area, preferably less than 25% relative to the total area, more preferably less than 20% relative to the total area, even more preferably less than 10% relative to the total area, and most preferably less than 5% relative to the total area. According to a preferred embodiment, the solid sulfide electrolyte according to the present invention has a peak area of ? as measured by NMR (preferably 31 P NMR) determined at least 70% pure, preferably at least 75% pure, more preferably at least 80% pure, even more preferably at least 90% pure, most preferably at least 95% pure. As will be appreciated by those skilled in the art, PS4 3- With a signal between 80 ppm and 90 ppm, preferably about 85 ppm, as indicated by 31 PNMR determined; PO4 3- With a signal between 5 ppm and 15 ppm, preferably about 10 ppm, as indicated by 31 P determined by NMR; PSO3 3- With a signal between 30 ppm and 40 ppm, preferably about 35 ppm, as indicated by 31 P determined by NMR; PS2O2 3- With a signal between 65 ppm and 75 ppm, preferably about 70 ppm, as indicated by 31 P determined by NMR; and P2S7 4- With a signal between 90 ppm and 100 ppm, preferably about 95 ppm, as indicated by 31 Determined by P NMR.
[0092] A preferred embodiment is a solid sulfide electrolyte according to the invention having an ionic conductivity of at least 1 mS / cm, preferably at least 1.5 mS / cm, most preferably at least 2 mS / cm. A preferred embodiment is a solid sulfide electrolyte according to the invention having an ionic conductivity of less than 5 mS / cm, more preferably less than 4 mS / cm, most preferably less than 3 mS / cm. A preferred embodiment is a solid sulfide electrolyte according to the invention having an ionic conductivity between 1 mS / cm and 5 mS / cm, preferably between 1.5 mS / cm and 4 mS / cm, most preferably between 2 mS / cm and 3 mS / cm.
[0093] A preferred embodiment is a solid sulfide electrolyte according to the present invention having a -7 mS / cm, preferably at least 1x10 -6 mS / cm, most preferably at least 1x10 -5 A preferred embodiment is a solid sulfide electrolyte according to the present invention, which has an electronic conductivity of less than 1x10 -2 mS / cm, preferably less than 1x10 -3 mS / cm, most preferably less than 1x10 -4 A preferred embodiment is a solid sulfide electrolyte according to the present invention, which has an electronic conductivity of between 1x10 -7 mS / cm vs 1x10 -2 mS / cm, preferably between 1x10 -6 mS / cm vs 1x10 -3 mS / cm, preferably between 1x10 -5 mS / cm vs 1x10 -4 Electronic conductivity between mS / cm.
[0094] Battery
[0095] A fourth aspect of the present invention relates to a battery comprising a negative electrode, a positive electrode and a solid electrolyte layer, wherein at least one of the cathode, the anode and the solid electrolyte layer comprises a solid sulfide electrolyte according to the present invention, such as a solid sulfide electrolyte obtainable by the method according to the present invention and / or a solid sulfide electrolyte having an argyrodite-type crystal structure according to the present invention. The solid sulfide electrolyte of the present invention can be used as a solid electrolyte layer of a solid lithium ion battery or a solid lithium primary battery, or as a solid electrolyte mixed with an electrode mixture for a positive electrode or a negative electrode.
[0096] As understood by those skilled in the art, the negative electrode is the anode and the positive electrode is the cathode. Thus, the present invention relates to a battery comprising a negative electrode, a positive electrode and a solid electrolyte layer, wherein at least one of the positive electrode, the negative electrode and the solid electrolyte layer comprises a solid sulfide electrolyte according to the present invention.
[0097] In a preferred embodiment, the battery is a solid state battery, preferably a lithium solid state battery.
[0098] use
[0099] A fifth aspect of the present invention relates to use of a solid sulfide electrolyte according to the present invention (such as a solid sulfide electrolyte obtainable by a method according to the present invention and / or a solid sulfide electrolyte having an argyrodite-type crystal structure according to the present invention) in a battery (preferably a solid-state battery, more preferably a lithium solid-state battery).
[0100] A sixth aspect of the invention relates to the use of a battery according to the invention in any of a portable computer, a tablet computer, a mobile phone, an energy storage system, an electric vehicle or in a hybrid electric vehicle, preferably in an electric vehicle or a hybrid electric vehicle.
[0101] The present invention is further illustrated in the following examples.
[0102] Example
[0103] Description of the test method
[0104] XRD analysis
[0105] Crystalline phase identification was performed using a Bruker D8 Advanced diffractometer with Cu radiation (λ1 = 1.54056 Å, λ2 = 1.54439 Å). Stainless steel cells with beryllium windows were used to prevent air exposure.
[0106] Ionic conductivity
[0107] Ionic conductivity was measured on a pellet cell pressed at 5 T on a sample with a diameter of 10 mm and a total sample mass of 120 mg. The pellet was transferred to a plastic sleeve (10.2 mm in diameter) with a stainless steel plunger with carbon paper on both sides. A metal clamp and torque wrench were used to tighten the 80 kg / cm 2 applied on the plunger. The ionic conductivity was measured using electrochemical impedance spectroscopy (EIS) in the range of 1 Hz to 30 MHz at room temperature (25 °C) using a MTZ-35 impedance analyzer from Biologic.
[0108] Electronic conductivity
[0109] Electronic conductivity was measured by chronoamperometry at 25°C on the same samples as ionic conductivity via stepwise potentiostatic polarization at 0.2 V, 0.4 V, 0.6 V and 0.8 V.
[0110] NMR analysis
[0111] NMR spectra were acquired over the temperature range of 100 K to 300 K using a Bruker 400 MHz (9.4 T) Ascend DNP-NMR spectrometer equipped with a 3.2 mm MAS DNP-NMR triple-resonance broadband X / Y / H magic angle spinning (MAS) probe spinning simultaneously at a rate of 8 kHz. At each temperature point, the sample temperature was calibrated using the T1 of 79Br in KBr. (35) For 23Na measurements, the probe was tuned to 105.9 MHz and a zg experiment with 6 µs π / 2 pulses at 10 W was used to selectively excite the central transition. The recycle delay was set to 40 s. The 23Na spectra are reported relative to the chemical shift of a 1.0 M solution of NaCl in water set to 0 ppm. For 31 P spectra, the probe was tuned to 162.0 MHz and a zg experiment with a π / 6 pulse of 1 µs at 160 W was used. The recycle delay was set to 200 s. Chemical shifts are reported relative to solid triphenylphosphine set to -9 ppm. 31 P spectra. Quantification of the different phases was performed by fitting in Origin (Pseudo-Voigt) and then calculating the phase percentages from the peak areas. Alternatively, the measurements were performed on a 500 MHz (11.7 T) WB (wide bore) Bruker Avance NMR spectrometer (for solids) using a 2.5 mm double resonance broadband probe spinning at 30 kHz. 31 P measurements. The experiments were run using the spin echo pulse program. Depending on the sample, a relaxation delay of 10 or 20 seconds was used. ”
[0112] Example
[0113] A precursor mixture containing lithium sulfide (Li2S, 0.1712 g), lithium chloride (LiCl, 0.1580 g) and lithium thiophosphate (Li3PS4, 0.6709 g) was prepared in a 1:1:1 molar ratio. The precursor mixture was added to a glass container with a liquid (20 mL). The total solid content was about 5% based on the total weight of the mixture. Table 1 shows all the tested liquids, their water content as determined by Karl-Fish titration, and the solubility of LiCl, Li2S, Li3PS4 and Li6PS5Cl in these solvents, where "yes" means that the corresponding compound is completely dissolved, "partially" means that the corresponding compound is partially dissolved, and "no" means that the corresponding compound is not dissolved. The resulting solution was stirred at 25 ° C for 24 h. The solvent was then removed by evaporation using a rotary evaporator. The resulting mixture was then further dried under vacuum, with the temperature gradually increasing by 80 ° C for 1 hour, 100 ° C for 1 hour, and 150 ° C for 18 hours. Figure 1 The XRD spectrum before calcination is shown: CEX1 observed the formation of Li6PS5Cl; CEX2 only observed LiCl and Li2S without Li6PS5Cl formation; EX1-5 did not observe Li6PS5Cl formation; beryllium peak (Be) comes from the sample holder with a beryllium window. The dried mixture was then pressed into pellets and calcined at 525°C for 6 hours in a stainless steel autoclave with an alumina crucible (wherein the temperature rise time was 2 hours, 4.2°C per minute) to obtain Li6PS5Cl. Table 2 shows the results of the ionic and electronic conductivity of each solvent. Figure 2 The XRD spectra after calcination are shown: for CEX1-2 and EX1-5, Li6PS5Cl was observed. XRD analysis proved that EX1 had 78.95% Li6PS5Cl, 4.78% Li2S, 1.75% LiCl and the remaining decomposition products; EX3 had 71.46% Li6PS5Cl, 6.17% Li2S, 1.95% LiCl and the remaining decomposition products; EX4 had 74.35% Li6PS5Cl, 5.82% Li2S, 1.80% LiCl and the remaining decomposition products, and EX5 had 77.83% Li6PS5Cl, 4.18% Li2S, 2.85% LiCl and the remaining decomposition products. Figure 3 The results of EX1 before calcination and CEX1 before calcination are shown. 31 P NMR spectra. Quantification of the peak areas (see Table 3) shows that the reaction in EtOH before calcination produces higher amounts of degradation products, especially with PSO3 compared to DMF as a liquid. 3- degradation products of the unit. 31P NMR analysis showed that EX1 after calcination had 98.7% PS4 3- Unit and 1.2% PO4 3- unit.
[0114] Table 1: List of solvents, their water content, and the solubility of LiCl, Li2S, Li3PS4, and Li6PS5Cl in the solvents.
[0115]
[0116] 1 Determined by Karl-Fisher titration
[0117] 2 Undetermined
[0118] 3 Dimethoxyethane
[0119] Table 2: Ionic and electronic conductivity of CEX1-2 and EX1-5
[0120]
[0121] 1 Undetermined
[0122] Table 3: Phases of EX1 and CEX1 before calcination 31 P NMR quantification.
[0123]
Claims
1. A method for producing a solid sulfide electrolyte, the method comprising the following consecutive steps: (i) providing an electrolyte precursor mixture comprising a solid electrolyte precursor mixture and a liquid, wherein the solid electrolyte precursor mixture comprises Li2S, Li3PS4 and LiX, and the liquid does not contain a hydroxyl moiety; (ii) mixing the electrolyte precursor mixture obtained in step (i); and (iii) heat treating the mixed electrolyte precursor mixture obtained in step (ii) to obtain a solid sulfide electrolyte having an argyrodite-type crystal structure; wherein X is a halogen selected from F, Cl, Br, I or a combination thereof.
2. The method of claim 1, wherein the liquid not comprising hydroxyl moieties is an organic liquid.
3. The method according to claim 1 or 2, wherein the liquid not containing a hydroxyl moiety is selected from: hydrocarbons, esters, ketones, aldehydes, ethers, nitriles, amines, amides, carbonates, sulfoxides, sulfones, sulfonates, thiols, fluorine-based compounds and combinations thereof, preferably selected from: aromatic hydrocarbons, esters, ethers, nitriles, amides, sulfoxides, thiols and combinations thereof, more preferably selected from: amides, esters, ethers, nitriles, aromatic hydrocarbons and combinations thereof.
4. The method according to any one of the preceding claims, wherein step (ii) further comprises the following steps: (ii) a mixing the electrolyte precursor mixture obtained in step (i), and (ii)b Drying the mixed electrolyte precursor obtained in step (ii)a to obtain a solid electrolyte mixture.
5. The method for producing the solid sulfide electrolyte according to any one of the preceding claims, wherein the solid sulfide electrolyte is represented by formula (I): Li 7-y P.S. 6-y X y (I), wherein y is from 0.8 to 1.7, preferably y is 0.9 or more and 1.6 or less, more preferably y is 1.0 or more and 1.4 or less.
6. The method for producing the solid sulfide electrolyte according to any one of the preceding claims, wherein the solid sulfide electrolyte is represented by formula (II): Li6PS5X(II).
7. The method for producing the solid sulfide electrolyte according to any one of the preceding claims, wherein the mixing of the electrolyte precursor mixture is carried out with a mixing time of between 1 hour and 72 hours, preferably between 2 hours and 50 hours, more preferably between 10 hours and 30 hours.
8. The method for producing the solid sulfide electrolyte according to any one of the preceding claims, wherein the molar ratio of Li2S:Li3PS4:LiX is 1:1:
1.
9. The method for producing the solid sulfide electrolyte according to any one of the preceding claims, wherein X=Cl, Br, I or a combination thereof; more preferably X=Cl, Br or a combination thereof; most preferably X=Cl.
10. The method for producing the solid sulfide electrolyte according to any of the preceding claims, wherein the heat treatment is performed at a temperature between 100°C and 1000°C, preferably between 300°C and 700°C, more preferably between 350°C and 650°C.
11. The method for producing the solid sulfide electrolyte according to any one of the preceding claims, wherein the heat treatment is performed for between 0.5 hours and 24 hours, preferably between 1 hour and 12 hours, more preferably between 1.5 hours and 10 hours.
12. A solid sulfide electrolyte obtainable by the method according to any one of claims 1 to 11.
13. A solid sulfide electrolyte having an argyrodite-type crystal structure, the solid sulfide electrolyte having a purity exceeding 70% as determined via XRD.
14. The solid sulfide electrolyte according to claim 13, wherein the solid sulfide electrolyte has 31 At least 95% pure as determined by PNMR.
15. The solid sulfide electrolyte according to claim 13 or 14, wherein the solid sulfide electrolyte is represented by formula (I): Li 7-y P.S. 6-y X y (I) wherein y is from 0.8 to 1.7, preferably y is 0.9 or more and 1.6 or less, more preferably y is 1.0 or more and 1.4 or less. 16 . A battery comprising a negative electrode, a positive electrode, and a solid electrolyte layer, wherein at least one of the positive electrode, the negative electrode, and the solid electrolyte layer comprises the solid sulfide electrolyte according to claim 12 .
Citation Information
Patent Citations
Method for producing solid electrolyte
US20190074544A1
Method of preparing sulfide-based solid electrolyte for all-solid battery having argyrodite-type crystal structure
US20190173127A1
Method of manufacturing solid electrolyte for all-solid cells, solid electrolyte manufactured using the method, and all-solid cell including the solid electrolyte
US20200119394A1